Influence of the 4600A/G and 4678G/C polymorphisms in the endothelial protein C receptor (EPCR) gene on the risk of venous thromboembolism in carriers of factor V Leiden - Medina, Pilar; Navarro, Silvia; Estellés, Amparo; Vayá, Amparo; Bertina, Rogier M.; España, Francisco (Thrombosis and Haemostasis, 2005)
Two polymorphisms in the endothelial protein C receptor (EPCR) gene, 4600A/G and 4678G/C, have been reported to influence the risk of venous thromboembolism (VTE). The objective of this study was to assess whether these polymorphisms modify the risk of VTE in carriers of factor V (FV) Leiden. We genotyped 295 carriers of FV Leiden for these polymorphisms: 100 unrelated patients with a history ofVTE (propositi) and 195 relatives (14 of them symptomatic) of 81 of the propositi. Spontaneous VTE events occurred in 71% of propositi carrying the 4678GG genotype, 65% carrying the GC, and 43% with the CC genotype. The mean age at the first onset was significantly higher in propositi carrying the 4678CC than in those with the GC or GG genotype (p=0.046). Among the 276 carriers of FV Leiden from the 81 families studied, the 95 symptomatic members had similar 4600G allele and 4600AG genotype frequencies but significantly lower 4678C allele (p=0.002) and 4678CC genotype (p=0.004) frequencies than the 181 asymptomatic members. The probability of being free of thrombosis at age 40 was significantly higher in the 66 carriers of the 4678CC genotype (94%) than in the 138 carrying the GC (72%) or in the 72 with the 4678GG genotype (60%) (p<0.001). Multivariate analysis showed that the 4678CC genotype reduced the risk of thrombosis in carriers of FV Leiden (OR=0.31;95% CI=0.16–0.83). The incidence ofVTE was higher in the 195 relatives with FV Leiden than in the 133 without FV Leiden (OR=4.7; CI=1.3–7.2). These results show that carriers of FV Leiden with the 4678CC genotype have a significantly reduced risk of VTE compared with those carrying the 4678GG or GC genotype, probably due to the higherAPC levels previously observed in individuals carrying the 4678CC genotype.
Keywords: Endothelial protein C receptor; factor V Leiden; venous thromboembolism; polymorphisms; survival time; interaction